Quantifying the Training Loads and Corresponding Changes in Physical Qualities among Adolescent, Schoolboy Rugby League Players - Michael A. Carron; Aaron T. Scanlan; Thomas M. Doering (MDPI AG, 2024)
Objectives: The adolescent development period is critical for rugby league athletes, given the physical growth, neuromuscular adaptation, and skill acquisition that occurs. Secondary schools play an important role in the development of adolescent rugby league players; however, players may be selected into rugby league academies and development programs outside of school, as well as participating in additional sports. In turn, the training loads these young athletes accrue and the implications of these loads are currently unknown. Our aim was to quantify the training loads and concomitant changes in physical qualities of schoolboy and adolescent rugby league players during mesocycles within the pre-season and in-season phases. Design: This is a prospective experimental study. Methods: Twenty-one schoolboy rugby league players (16.2 ± 1.3 years) were monitored across separate 4-week mesocycles in the pre-season and in-season. Session frequency, duration, and the session rating of perceived exertion (sRPE) load were reported for all examples of training and match participation in the school rugby league program, as well as club and representative teams for any sport and personal strength and conditioning. Various physical qualities were assessed before and after each 4-week mesocycle. Results: The sRPE load that accumulated across the 4-week mesocycles was higher in the pre-season than the in-season (8260 ± 2021 arbitrary units [AU] vs. 6148 ± 980 AU, p < 0.001), with non-significant differences in accumulated session frequency and duration between phases. Session frequency, duration, and sRPE load differed (p < 0.05) between some weeks in an inconsistent manner during the pre-season and in-season mesocycles. Regarding physical qualities, improvements (p < 0.05) in the 10 m sprint test, Multistage Fitness Test, medicine ball throw, and 1-repetition maximum back squat and bench press performances were evident across the pre-season mesocycle, with declines (p < 0.05) in the 505-Agility Test, L-run Test, and 1-repetition maximum back squat performances across the in-season mesocycle. Conclusions: These novel training load data show schoolboy rugby league players experience considerable demands that may be suitable in developing several physical qualities during the pre-season but detrimental to maintaining such qualities across the in-season.